ANALISIS MANAJEMEN LABA DAN KINERJA KEUANGAN PERUSAHAAN PENGAKUISISI SEBELUM DAN SESUDAH AKUISISI - Tyasshela Sani Wibowo (Universitas muhammadiyah malang, 2015)
This study discuss about earnings management and financial performance of the acquirer before and after acquisition. The purpose of research was to obtain empirical evidence of how earning management have done by acquirer companies before the implementation of acquisition. In addition it aims to determine the changes in the acquirer’s financial performance before and after the acquisition. This research is a comparative study which to compare the financial performance the acquirer before and after the company make acquisition. Analysis of financial performance uses financial rations, including profitability, activity, and solvability. Analysis of earnings management using the theory of Jones modified. Earnings management by the acquirer is a proxy for discretionary accruals (DA). The company performance was measured by using financing rations (a net profit margin, return on assets, total assets turnover, and debt to equity ratio). The result of analysis showed that there are two companies which have positive discretionary accrual value and the other three companies which have negative discretionary accrual value. Moreover financial performance of the acquirer company is experiencing the different more toward to reduction of financial performance. The conclusion was that earning management of two acquirer companies (ANTM and UNTR) have done by increasing the profit (income increasing accruals) before doing the acquisition. While, the other three companies (ENRG, RAJA, and SMGR) have done earning management by decreasing the profit (income decreasing accruals) before doing the acquisition. Furthermore, financial performance that measure with NPM and DER increased after acquisition, while ROA and TATO decreased after acquisition.